TINJAUAN BIM (BUILDING INFORMATION MODELLING) DALAM BIDANG ICT KONSTRUKSI DI NEGARA ASEAN - Wisnu Adi Prasetya (Universitas Muhammadiyah Semarang, 2018)
This study discusses the current status of BIM implementation in ASEAN countries. Based on a review of recent research, this article focuses on the question of what is the current status of BIM implementation in ASEAN countries, and what further research is needed to advance the implementation of BIM? Addressing these questions makes researchers and practitioners focused on construction companies operating in ASEAN countries, seeking the benefits of BIM. Keywords: ICT, BIM, Building Information Modelling, Construction, ASEAN